2003
DOI: 10.1002/ijc.11471
|View full text |Cite
|
Sign up to set email alerts
|

Increase of AKT/PKB expression correlates with gleason pattern in human prostate cancer

Abstract: Key words: AKT/protein kinase B; prostate; adenocarcinoma; tumor grade; immunohistochemistryProstate cancer (prostatic adenocarcinoma) is one of the most frequent malignancies and the second-leading cause of cancer mortality in males in Western countries including Germany. [1][2][3] Although prostate cancer is often an indolent disease, 25-30% of the tumors behave aggressively 2 resulting in poor prognosis and eventually in the death of the patients. The present stage of knowledge often does not permit a decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 18 publications
4
72
0
Order By: Relevance
“…Some authors have shown that AKT is upregulated in prostate cancer compared with benign prostatic tissue (BPT), prostatic intraepithelial neoplasia (PIN) and primary tumors graded 2-5 according to Gleason. 33,34 Interestingly, no change in the degree of AKT expression was detected in studies in which tumors had Gleason scores ranging from 6 to 10. 35,36 On the other hand, the staining intensity for pAKT has been reported to be significantly greater in prostate tumors with high Gleason grade (Gleason 8-10).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown that AKT is upregulated in prostate cancer compared with benign prostatic tissue (BPT), prostatic intraepithelial neoplasia (PIN) and primary tumors graded 2-5 according to Gleason. 33,34 Interestingly, no change in the degree of AKT expression was detected in studies in which tumors had Gleason scores ranging from 6 to 10. 35,36 On the other hand, the staining intensity for pAKT has been reported to be significantly greater in prostate tumors with high Gleason grade (Gleason 8-10).…”
Section: Discussionmentioning
confidence: 99%
“…80,85 Elevated Akt expression and kinase activities are associated with a hormone-resistant phenotype and correlates with a poor prognosis in human prostate cancer and breast cancer. 78,79,85,86 Upstream of Akt, amplification of PI3-K has been reported for prostate, 79 ovarian, 87,88 colon, 88 and breast cancer. 85 Several protein-tyrosine kinases (PTKs), which act upstream of the PI3-K and are important regulators of the PI3-K-Akt pathway, have been found overexpressed in various cancers because of activating mutations or other genetic alterations.…”
Section: Genetic Perturbation and Dysregulation Of The Pi3-k-akt Pathwaymentioning
confidence: 99%
“…There are three members of the Akt family, Akt1, -2 and -3, and evidence suggests that the three isoforms of Akt have different roles in the development of hormone-resistant breast cancer either via interactions with the oestrogen receptor or via proteins involved in proliferation and apoptosis, for example, mTOR and BAD (Kirkegaard et al, 2005). Akt may play a similar role in the development of HRPC (Liao et al, 2003). Cell line studies demonstrate that low passage LNCaP cells (hormone-sensitive prostate cancer cells) have low basal Akt activity, possibly due to early-stage prostate cancer relying on hormones for growth and survival.…”
mentioning
confidence: 99%
“…Prostate tumours are reported to have significantly higher Akt expression than BPH (Liao et al, 2003), and only 10% of well-differentiated prostate tumours strongly express pAkt compared to 92% of poorly differentiated tumours (Malik et al, 2002;Ayala et al, 2003;Ghosh et al, 2003). Akt1 and Akt2 expression in hormone-sensitive tumours have been associated with shorter time to biochemical relapse; however, no association was reported with the activated forms or with survival (Le Page et al, 2006).…”
mentioning
confidence: 99%